Novel Insights into the Molecular Interaction of a Panduratin A Derivative with the Non Structural Protein (NS3) of Dengue Serotypes: A Molecular Dynamics Study - Parida, Pratap; Yadav, Raj N. S.; Dehury, Budheswar; Ghosh, Debosree; Mahapatra, Namita; Mitra, Analava; Mohanta, Tapan K. (Current Pharmaceutical Biotechnology, 2017)
Background: The ligand PKP10 having substitution of Cl- at R2 and R3 positions of ring A of Panduratin A i.e., ((1R,2S,5S)-5-(2,3-dichlorophenyl)-3-methyl-2-(3-methylbut-2-nyl)cyclohex-3- enyl)(2,6-dihydroxy-4-methylphenyl)methanone hydrate) has been observed to block the Nuclear Receptor Binding Protein binding site of Non Structural protein 3 in all dengue serotypes. In continuation with our earlier study, we have reported sixty novel Panduratin A derivatives compounds where substitution was done in positions 2 and 3 position of the benzyl ring A of Panduratin A with various substituents. Methods: We selected ((1R,2S,5S)-5-(2,3-dichlorophenyl)-3-methyl-2-(3-methylbut-2-nyl)cyclohex-3- nyl) (2,6-dihydroxy-4-methylphenyl) methanone hydrate) (PKP10) for molecular dynamics (MD) simulations as it constantly produced lowest CDocker interaction energy of among all the sixty five derivatives. The CDocker interaction energy was predicted to be -140.804, -79.807, -78.217 and -84.073 Kcalmol-1 respectively against NS3 protein of dengue serotypes (DENV1-4). To understand the dynamics of the PKP10 with NS3 protein, each complex was subjected to molecular dynamics simulations of 50 ns in aqueous solution. MD (Molecular Dynamics) simulation study revealed that the binding of ligand PKP10 at the active site of NS3 induces a conformational change in all serotypes which was well supported by principal component analysis. Result: To the best of our knowledge, this is first ever study which provided atomistic insights into the interaction of PKP10 with NS3 protein of dengue serotypes. Conclusion: The result from our study along with in vitro studies is expected to open up better avenues to develop inhibitors for dengue virus in the near future.
Keywords: panduratin A